2013
DOI: 10.1182/blood-2012-07-442590
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-mediated siRNA delivery for targeting of normal and malignant human hematopoietic cells in vivo

Abstract: • CpG(A)-siRNA oligonucleotides allow for targeting genes specifically in human TLR9 ϩ immune cells and blood cancer cells.• Tumoricidal and immunostimulatory properties of CpG(A)-STAT3 siRNA provide a novel therapeutic opportunity for hematologic malignancies.STAT3 operates in both cancer cells and tumor-associated immune cells to promote cancer progression. As a transcription factor, it is a highly desirable but difficult target for pharmacologic inhibition. We have recently shown that the TLR9 agonists CpG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 52 publications
5
119
0
Order By: Relevance
“…Being a transcription factor, Stat3 is a difficult target to inhibit in a cell-specific manner. However, recent approaches to inhibit Stat3 using targeted platforms to deliver siRNA to specific immune cells have been explored with therapeutic success by our group (16,36,37). Thus, in addition to more potent and innovative small molecule inhibitors of Stat3 signaling in the near future, targeting Stat3 specifically in T cells may be an ultimate goal for treating obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Being a transcription factor, Stat3 is a difficult target to inhibit in a cell-specific manner. However, recent approaches to inhibit Stat3 using targeted platforms to deliver siRNA to specific immune cells have been explored with therapeutic success by our group (16,36,37). Thus, in addition to more potent and innovative small molecule inhibitors of Stat3 signaling in the near future, targeting Stat3 specifically in T cells may be an ultimate goal for treating obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…16, 17 We later demonstrated that CpG-ODNs can be used for cell-specific small interfering RNA (siRNA) delivery as CpG-siRNA conjugate to silence genes in mouse and human TLR9-positive cells. [18][19][20] Here, we assessed whether systemically administered CpG-Stat3 siRNA would generate antitumor effects against a genetic mouse model of Cbfb-MYH11/Mpl 1 (CMM 1 )-induced leukemia, which closely mimics human AML with inv(16)(p13:q22) gene fusion in 10% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…We recently described a technology for efficient in vivo delivery of siRNA into immune cells by linking an siRNA to CpG oligonucleotide, which binds to its cognate receptor, TLR9 (21). TLR9 is expressed intracellularly in cells of myeloid lineage and B cells as well as tumor cells expressing TLR9, including human leukemic cells (21,22). However, the CpGsiRNA approach does not directly target T cells (21).…”
Section: Introductionmentioning
confidence: 99%